Pengembangan Usaha Kuliner Tahu Walik Melalui Pendekatan Kewirausahaan - Syariah Hafizhoh; Fithri Asmelia; Muhammad Akbar Thoha; Arif Rahman Hakim; Amaliah Nurhanisah Gultom; Nur Ikhsan Kharisma Sitorus; Siti Ardiyanti; Khaidah Try Apnisyah Sitorus; Dwi Nur Luthfiah (Universitas Maritim AMNI Semarang, 2023)
Culinary business is an economic sector that continues to grow, especially in the food business made from Tahu Walik. This study aims to explore and analyze the development potential of Tahu Walik culinary businesses through an entrepreneurial approach. Data were collected through in-depth interviews with business owners and direct observation at the business location related to marketing and management strategies that have been implemented. The results showed that the entrepreneurial approach plays an important role in the development of the Tahu Walik culinary business. In addition, there is the potential and uniqueness of Tahu Walik as a culinary product as well as supporting factors and obstacles in the implementation of the Tahu Walik culinary business. By utilizing the potential and uniqueness of the product and overcoming existing obstacles, the Tahu Walik industry can continue to grow and contribute to the preservation of Indonesia's culinary culture and the country's economic growth.